More Than Just a Bandage: Closing the Gap Between Injury and Appendage Regeneration - Kakebeen, Anneke D.; Wills, Andrea E. (Frontiers in Physiology, 2019)
The remarkable regenerative capabilities of amphibians have captured the attention of biologists for centuries. The frogs Xenopus laevis and Xenopus tropicalis undergo temporally-restricted regenerative healing of appendage amputations and spinal cord truncations, injuries that are both devastating and relatively common in human patients. Rapidly expanding technological innovations have led to a resurgence of interest in defining the factors that enable regenerative healing, and in coupling these factors to human therapeutic interventions. It is well-established that early embryonic signaling pathways are critical for growth and patterning of new tissue during regeneration. A growing body of research now indicates that early physiological injury responses are also required to initiate a regenerative program, and that these differ in regenerative and non-regenerative contexts. Here we review recent insights into the biophysical, biochemical, and epigenetic processes that underlie regenerative healing in amphibians, focusing particularly on tail and limb regeneration in Xenopus. We also discuss the more elusive potential mechanisms that link wounding to tissue growth and patterning.